Students' High-Level Thinking Ability In Learning Mathematics In The Era Of Pandemic Covid-19 - Yazidah, Nok Izatul; Argarini, Dian Fitri; Sulistyorini, Yunis (Universitas Malikussaleh, 2021)
High-level thinking skills are an ability that students must have to support how students can think creatively and critically. But what about the learning process in the Covid-19 pandemic era, which can still pay attention to students' higher-order thinking skills. This study aims to describe the learning process in the Covid-19 era in junior high schools in Malang district, and how the students' high-level thinking skills. The data collection methods used were interviews and tests. The research data obtained during the study shows that teachers have maximized the use of online learning platforms to support the virtual learning process recommended by the government. In addition, it was found that the high level thinking ability of junior high school students in Malang district had met the minimum standard set by the researcher at 75%.